Development of STEM-Based Flipbook Learning Media on the Bloodstream System Materials for Junior High School - Munandar, Rifki Risma; Suhardi, Eka; Husna, Melsa Nazmaul (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study aims to develop The STEM-based flipbook learning media on the Human Circulatory System material for junior high school students. This study uses research and development methods or Research and Development (R&D) with the ADDIE research model and involves 7 validators to validate flipbook learning media. This research instrument uses a validation sheet consisting of a content validation sheet, media validation sheet, material validation sheet, language validation sheet and media and content validation sheet with analytical techniques using quantitative descriptive analysis. The results of this study are the development of STEM-based Flipbook learning media has been declared feasible with an average score of 81%. The criteria are very valid and get positive results from various validators. Based on the validation results, it shows that the learning media developed is suitable for use in learning, because the media has features (videos, quizzes, and STEM LKPD) that can be accessed online.